Analisis sikap konsumen atas kreatfitas iklan, daya tarik iklan dan kualitas pesan iklan pada handphone merek Sony Xperia Z di kota Pekanbaru - Suryanto Primanaldi; Zulkarnain '; Marhadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to look at consumer attitudes on advertising creativity, attraction advertising and quality of the advertising message on Sony Xperia Z in Pekanbaru city. The population in this study are the people who use and watch Sony Xperia Z’s ad in Pekanbaru city. While the sample in this study using purposive sampling method with criteria people who live in Pekanbaru city with the age of 15-30 years who using and watching Sony Xperia Z’s ad. The data obtained will be processed by Fishbein analysis. After the test, the results is consumer attitudes toward advertising creativity is very good, this is evidenced by the performance of advertising creativity has reached what is perceived by the respondents. Consumer attitudes toward attraction advertising is very good, this is evidenced by the performance of the attraction of advertising has reached what is perceived by the respondents. And consumer attitudes toward quality of the advertising message is also very good, this is evidenced by the performance of quality of the advertising message has reached from what is perceived by the respondents.Keywords: advertising creativity, attractiveness and quality of advertising message.